Characterization of Catalyst Coated Membranes using Electron and X-ray Microscopy - Guimarães de Azeredo Melo, Lis (My University, 2014)
Proton-Exchange Membrane Fuel Cells are an alternative source of electricity generation for automobiles and stationary power plants. With increasing concerns on environmental issues, recent research has focused on maximizing the efficiency and durability as well as minimizing the costs of fuel cells. One of the main areas of research is optimizing the structure of the cathode catalyst layer. The main driving force of this thesis was the effective visualization of nanostructure of the ionomer, which is responsible for proton conduction in the cathode catalyst layer. However, challenges regarding sample preparation and radiation damage still need to be well understood. Different sample preparation techniques of catalyst inks and catalyst coated membranes were used for Scanning and Transmission Electron Microscopy, such as freeze fracturing, ultramicrotomy and Focused Ion Beam. Comparisons of the microstructure and chemical differences of all components, especially the ionomer, prepared by ultramicrotomy and Focused Ion Beam, was done with Transmission Electron Microscopy and Scanning Transmission X-ray Microscopy applied to the same catalyst coated membrane sample. Detailed spectroscopic information regarding components in both specimens was compared with C 1s and F 1s near edge X-ray absorption spectra recorded in a Scanning Transmission X-ray Microscope. Focused Ion Beam causes extensive damage to the carbon support and ionomer but prepares thinner sections than ultramicrotomy. This work makes it possible to understand the limitations of each sample preparation and compositional analysis technique in order to later apply one of them to image the ionomer in the catalyst layer at the nanoscale, hopefully using tomography techniques.
Keywords: Proton exchange membrane fuel cell; Transmission Electron Microscopy; Scanning Transmission Electron Microscopy; Ionomer; Focused Ion Beam